Mercury and Methylmercury Contamination of Terrestrial and Aquatic Ecosystems - Guédron, Stéphane; Acha, Dario (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue aims to provide new insights into the issue of the mercury contamination of terrestrial and aquatic ecosystems. This ubiquitous contaminant has been used by humans for many years, resulting in global contamination. When this toxic contaminant is converted to methylmercury, it accumulates in trophic chains, which is a major issue for wildlife and human health. The nine articles contained within this Special Issue on ''Mercury and Methylmercury Contamination of Terrestrial and Aquatic Ecosystems'' endeavour to identify the historical evolution of Hg and MeHg levels in aquatic environments, and to evaluate the impact of current and historical human activities, such as mining, climate change, and soil erosion, on receptor ecosystems and food chains.